The Global Cold War on Campus : Student Activism at Kabul University, 1964–1992 - Klausmann, Kyara Anne (ZMO-Studien, 2023)
How and why did students at Kabul University engage in political activism or refrained from it between 1964 and 1992? Based on oral history interviews with former students, this book reveals how they – as many others around the world at the same time – were galvanized by and disappointed with promises of progress dominating local and international politics. During the 1960s, the international influences on campus encouraged students’ engagement with competing political ideologies. Collective student protest against the monarchy turned into hostilities between opposing political groups within the student body claiming to lead Afghanistan towards independence and prosperity. After the coup d’état by the People’s Democratic Party of Afghanistan (PDPA) in 1978, none of the ideologies which had previously incited students provided hope for a better future anymore. Many students who had fought for the PDPA earlier were repelled by the government’s violence and those who stood up against the regime were persecuted and fled the country. Overall, the dynamics of political activism at Kabul University reflect the deep intertwinement of the Global Cold War and local struggles for inclusion and independence. ; How and why did students at Kabul University engage in political activism or refrained from it between 1964 and 1992? Based on oral history interviews with former students, this book reveals how they – as many others around the world at the same time – were galvanized by and disappointed with promises of progress dominating local and international politics. During the 1960s, the international influences on campus encouraged students’ engagement with competing political ideologies. Collective student protest against the monarchy turned into hostilities between opposing political groups within the student body claiming to lead Afghanistan towards independence and prosperity. After the coup d’état by the People’s Democratic Party of Afghanistan (PDPA) in 1978, none of the ideologies which had previously incited students provided hope for a better future anymore. Many students who had fought for the PDPA earlier were repelled by the government’s violence and those who stood up against the regime were persecuted and fled the country. Overall, the dynamics of political activism at Kabul University reflect the deep intertwinement of the Global Cold War and local struggles for inclusion and independence